2020
DOI: 10.1192/j.eurpsy.2020.67
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of client-therapist perspectives on the therapeutic alliance: Examining the moderating role of type of measurement and diagnosis

Abstract: Background: Clients and therapists often have different perspectives on their therapeutic alliance (TA), affecting the process and outcome of therapy. The aim of the present meta-analysis was to assess the mean differences between clients’ and therapists’ estimations of TA among clients with severe disturbances, while focusing on two potential moderators: client diagnosis and alliance instrument. Method: We conducted a systematic literature search of studies examining both client perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…A meta‐analytic examination of diverse mental conditions has shown client and therapist TA ratings were only moderately correlated ( r = .36) (Tryon et al, 2007). Furthermore, a recent meta‐analysis has shown that within the category of severe mental illnesses, diagnosis is not a moderator for lack of agreement or incongruence in ratings (Igra et al, 2020); thus, other factors are related to it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analytic examination of diverse mental conditions has shown client and therapist TA ratings were only moderately correlated ( r = .36) (Tryon et al, 2007). Furthermore, a recent meta‐analysis has shown that within the category of severe mental illnesses, diagnosis is not a moderator for lack of agreement or incongruence in ratings (Igra et al, 2020); thus, other factors are related to it.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that these findings reflected a ‘better safe than sorry’ pattern in which therapist caution may contribute to a greater likelihood of therapist underestimation of TA relative to the client, and better ability to track temporal changes more accurately. A meta‐analysis on studies among people with serious mental illness has confirmed a general trend for clients to rate the alliance somewhat higher than therapists (Igra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such qualities are reflective of Rogers' (1957, 1965) seminal work and the person‐centred literature whereby the constructs of empathy (Elliott et al, 2018), unconditional positive regard (Farber et al, 2018) and genuineness (Kolden et al, 2018) have been linked to psychotherapy outcome. Furthermore, client–therapist agreement on the therapeutic alliance can be integral to positive (Marmarosh & Kivlighan, 2012) or negative therapeutic outcomes (Rubel et al, 2018), although dependent on which outcome measure is used to assess alliance (Igra et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic alliance can be assessed by both client and therapist, but these assessments can differ. Interestingly, a pattern in which therapists systematically assess the alliance as lower than do their clients has been shown across different therapeutic approaches and different populations (Atzil‐Slonim et al, 2015; Hasson‐Ohayon et al, 2021; Igra et al, 2020; Marmarosh & Kivlighan, 2012; Shick Tryon et al, 2007). This discrepancy has been coined a ‘better safe than sorry’ approach on the part of therapists, as it implies a cautious attitude not to overestimate the TA and consequently fail to recognize ruptures (Atzil‐Slonim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, empirically assessing TA with dyadic indices, that is from both client and therapist points of view, is important as it allows us to broaden our understanding regarding TA and its effects (Coyne et al, 2018; Laws et al, 2017; Zilcha‐Mano et al, 2016). In addition, an aspect which seems particularly important in the assessment of TA effects on psychotherapy outcome is the effect of TA congruence—that is the level of agreement between client and therapist regarding TA across time (Igra et al, 2020)—on outcome.…”
Section: Introductionmentioning
confidence: 99%